REDESIGN OF IPUSNAS APPLICATION USING USER CENTERED DESIGN METHOD - Muhammad Rafi Pradana; Nuryuliani (International Journal Science and Technology, 2023)
The National Library of Indonesia (Perpusnas) is one of the libraries that already uses a Digital Library named Ipusnas. Ipusna provides access to literature available at National Library via smartphone. However, the Ipusnas application only gets a rating of 3.5 on the Google Playstore. This rating was obtained because the Ipusnas android application still has deficiencies, which is the User Interface and User Experience are still less modern and confusing in finding information. In this study, a redesign was developed using the User Centered Design method and Tested using A/B Testing. Results of the System Usability Scale Questionnaire From the calculation results using the System Usability Scale formula, the average score for evaluating the Ipusnas android application is 61.2. From the results of this SUS score, the research can be continued so that the Redesign of Ipusnas android application better than old one. Based on the evaluation results using the A/B Testing method, it can be concluded that users prefer the new design with a percentage value of 64% compared to the old design of 36%.